2018
DOI: 10.3390/e20120971
|View full text |Cite
|
Sign up to set email alerts
|

Landauer’s Principle as a Special Case of Galois Connection

Abstract: It is demonstrated how to construct a Galois connection between two related systems with entropy. The construction, called the Landauer’s connection, describes coupling between two systems with entropy. It is straightforward and transfers changes in one system to the other one, preserving ordering structure induced by entropy. The Landauer’s connection simplifies the description of the classical Landauer’s principle for computational systems. Categorification and generalization of the Landauer’s principle open… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…The Landauer Principle, suggesting the thermodynamic equivalent of information, attracted an essential interest of researchers in the last decade [1][2][3][4][5]. In its strictest, tightest, and simplest meaning, the Landauer principle states that the erasure of one bit of information requires a minimum energy cost equal to 2, where T is the temperature of a thermal reservoir used in the process and is Boltzmann's constant [6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The Landauer Principle, suggesting the thermodynamic equivalent of information, attracted an essential interest of researchers in the last decade [1][2][3][4][5]. In its strictest, tightest, and simplest meaning, the Landauer principle states that the erasure of one bit of information requires a minimum energy cost equal to 2, where T is the temperature of a thermal reservoir used in the process and is Boltzmann's constant [6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It has already been suggested that energy and information play a role in the life cycle of living organisms [ 26 ]. Kycia related the Landauer principle, which he treats as a special case of a more general Galois connection, to the DNA and RNA processing in vivo and in vitro [ 27 ].…”
Section: Viruses As Thermodynamic and Information Processing Systementioning
confidence: 99%
“…The kinetics of thermal inactivation of a virus is characterized by the rate of decrease of the substrate population defined as: where A is the virus population. The rate of thermal inactivation is governed by the Eyring equation: where h is the Planck constant, and is the change of the molar Gibbs energy of the population as it goes to the inactivated state, is the activation molar enthalpy, and is the activation molar entropy [ 27 ]. Therefore, the rate of inactivation of viruses increases dramatically with heating.…”
Section: Viruses As Thermodynamic and Information Processing Systementioning
confidence: 99%
“…The Landauer Principle, suggesting the thermodynamic equivalent of information, has attracted the interest of researchers in the last decade [ 1 , 2 , 3 , 4 , 5 ]. Simply put, the Landauer principle states that the erasure of one bit of information requires a minimum energy cost equal to , where T is the temperature of a thermal reservoir used in the process and is Boltzmann’s constant [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%